PENGARUH KESEHATAN, KESELAMATAN KERJA (K3) DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. MEGAKARYA MAKMUR SENTOSA KOTA DEPOK - Bakti Putra, Guntur; Nelsi, Mitri (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to find out whether there is an influence of health, K3 work safety and the work environment, either partially or simultaneously, on employee performance at PT Megakarya Makmur Sentisa, Depok City. This type of research uses an associative and quantitative approach in collecting samples using a saturated sampling technique because all members of the population in this research were used as samples, namely 80 employees. This research was conducted on employees of PT Megakarya Makmur Sentisa, Depok City. Based on partial research results (t test), it was concluded that health and safety at work K3 had a positive and significant effect on employee performance with a value of tcount > ttable or (4.748 > 1.990). Meanwhile, partially the work environment has a positive but not significant effect on employee performance with the value obtained tcount > ttable or (2.838 > 1.990). Based on the simultaneous regression test (F Test), the variables health, occupational safety, K3 and the work environment have a positive and significant effect on employee performance with the calculated F value > F table or (22.164 > 2.333), this is also reinforced by the ρ value < Sig 0.050 or (0.000 < 0.050).